EVALUATION OF SUPPLY CHAIN MANAGEMENT PROCESSES OF THE SERVICE SECTOR COMPANY - Balvočiūtė, Rasa (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The article presents the evaluation of the supply chain management of the service sector company using the expert evaluation methodology. The study identified seven strategic and operational supply chain processes in line with the model approved by the Global Supply Chain Forum. The gaps in supply chain processes between the intended and the actual state of management allowed to identify service disruptions and provide opportunities for processes improvement. Keywords: processes, sub-processes, strategic level, operational level, supply chain, gap.